The Relationship between Work Conditions and Performance and Satisfaction of Health Workers in the Inpatient Room of the Bahteramas Hospital Regional Public Service Agency - Ayu Sudirman, Putri; Saafi, La Ode; Helty, Helty (Waluya The International Science of Health Journal, 2024)
Introduction: Job satisfaction of State Civil Service health workers is a process of activities in the practice of health services directly to patients, to meet the basic needs of patients who are guided by the standards and ethics of good, optimal and professional health services. Preliminary surveys show that organizational policies are less than optimal, working conditions are less conducive and work performance has decreased, thus affecting performance in serving patients. This study aims to analyze the relationship between work conditions and performance with the satisfaction of health workers in the inpatient ward of the Bahteramas Hospital Regional Public Services Agency. Method: This research is quantitative using a Cross Sectional Study design, with a population of 213 people and a sample of 139 respondents using the Cluster Random Sampling technique. Result: The chi square statistical test at the 95% confidence level (α=0.05) shows that the p value = 0.006 because Ho is rejected or Ha is accepted, which means there is a relationship between working conditions and health worker satisfaction and the results of the chi square statistical test at the 95% confidence level (α=0.05) shows that the p value = 0.001 because Ho is rejected or Ha is accepted, which means there is a relationship between work performance and satisfaction of health workers. Conclusion: There is a relationship between working conditions and work performance and the performance of health workers in the inpatient ward of the Bahteramas Hospital Regional Public Services Agency.